Design and Implementation of a Flexible Mobile Edge Middleware for Multi-Protocol Wireless Connectivity - Reimer, Tatiana; Rios, Luis E. Talavera; Cavalcanti, Millena; Lucchesi, Laercio; Endler, Markus (2024 IEEE Conference on Pervasive and Intelligent Computing (PICom), 2024)
The widespread adoption of smartphones, especially in urban areas, play a central role in enabling novel participatory mobile IoT applications through their ubiquitous Internet connectivity and embedded sensors. They act as central nodes to communicate with short-range wireless IoT devices. In these scenarios, smartphones can serve as all-purpose hubs for interacting with wireless IoT devices, sensors, actuators, or mesh networks that are equipped with exclusively short-range wireless connectivity. The study introduces M-Hub2, a Kotlin-based edge middleware for Android devices, capable of identifying nearby BLE, NFC, and Wi-Fi Direct devices, including sensors, actuators, beacons, and other related technologies. The component establishes connections to backend services and IoT applications opportunistically. The M-Hub2's key advancement from its previous version is its modular software architecture and support for various WWAN and WPAN protocols. Experiments utilized BLE, NFC, and Wi-Fi Direct sensors, with dynamic identification and communication by the M-Hub2. The study demonstrated that NFC and BLE devices established faster connections and NFC communication provided superior outcomes.